Leadership Style and Motivation Impact on Improve Teacher Performance - Kulsum, A D U; Wahdiniwaty, R (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This research aims to analyze the impact of leadership style and motivation to improve teacher performance. Research conducted in the field of education with teachers as research subjects. The data used in this research is primary data in the form of a questionnaire as well as secondary data obtained from various scientific literature such as academic journals, textbooks, and various documents from companies. Multiple linear regression was used to analyze respondents' answers, and the hypothesis was tested using the t-test and f-test. The results of the study show that teacher performance is significantly influenced by leadership style and the teacher's motivation. It means teacher performance will increase by applying leadership style and improving motivation for the teacher. This research is expected to have an impact on the improvement of teacher performance by applying the right leadership style to improve the motivation of the employee